Inventing Rising Topics in Social Networks through Link-Anomaly Detection - Sasikanth, A; Venkata Ramana, S (International Journal of Computer Sciences and Engineering, 2025)
Detection of rising topics is currently receiving revived interest impressed by the rapid climb of social networks. during this context, Conventional-term-frequency-based approaches might not be acceptable, as a result of the data changed in social-network posts embody not solely text however conjointly pictures, URLs, and videos. We have a tendency to specialize in emergence of topics signaled by social aspects of those networks. Specifically, we have a tendency to specialize in mentions of user links between users that are generated dynamically (intentionally or unintentionally) through replies, mentions, and retweets. we have a tendency to propose to notice the emergence of a replacement topic from the anomalies measured through the model and propose a chance model of the mentioning behavior of a social network user, and aggregating anomaly scores from many users, we have a tendency to show that we will notice rising topics solely supported the reply/mention relationships in social-network posts. we have a tendency to gathered from Twitter and incontestable the technique in many real knowledge sets. The experiments show that the projected mention-anomaly-based approaches will notice new topics a minimum of as early as text-anomaly-based approaches, and in some cases abundant earlier once the subject is poorly known by the matter contents in posts.